Blockchain in the New Era of Accounting: A PRISMA-Guided Review on Trends and Future Prospects - Kampiotis, Georgios; Thanasas, Georgios L.; Gorodyskiy, Mykola; Bereznyi, Oleksandr (Public Policy and Accounting, 2025)
This review synthesizes recent scholarships at the intersection of digital accounting and blockchain, examining how their integration reshapes financial reporting, auditing, and organizational performance. Following PRISMA 2020, we screen and analyze peer-reviewed studies published from 2023 through July 2025 across leading databases. Evidence indicates that digital accounting—driven by blockchain, artificial intelligence, cloud platforms, and robotic process automation—improves data accuracy, process efficiency, transparency, and fraud deterrence, enabling timelier, decision-useful information. At the same time, adoption is constrained by cybersecurity exposure, high implementation and maintenance costs, talent shortages, and change resistance. The literature also documents role reconfiguration: accountants are shifting from transactional data entry toward analytical, assurance, and advisory functions. Outcomes, however, are heterogeneous across regions and industries, reflecting differences in regulation, digital infrastructure, and organizational readiness. We conclude by outlining a research agenda on ethical governance and accountability, policy and standard-setting implications, curriculum and workforce development, and cross-cultural adoption dynamics to support sustainable, trustworthy digital transformation in accounting and auditing.